Checklist of amphipod crustaceans (Crustacea: Amphipoda) in Slovenia - Cene Fišer; Borut Mavrič; Marijan Govedič; Anja Pekolj; Maja Zagmajster (Natura Sloveniae)
Amphipods are among the most species-rich orders of peracarid crustaceans, inhabiting marine and fresh waters, including subterranean waters, as well as semi-terrestrial environments. Data on amphipods from Slovenia are scattered among published and unpublished references. We gathered all available data on amphipods in the country, using published and unpublished records from two databases, supplemented by additional published information and unpublished records from two collections of two institutions. All data were critically evaluated and species names updated to the latest taxonomically valid name. In total, we listed 198 species, belonging to 85 genera and 41 families. About two thirds of the species are marine, while the rest are semiterrestrial, brackish and freshwater species. Among the latter, subterranean species dominate. In total, 26 species endemic to Slovenia were identified, one of which lives in surface freshwater, and the rest in groundwaters. Surprisingly, no presence of invasive freshwater amphipod species has currently been confirmed. We provided critical comments on nine amphipod species that were listed erroneously for the country. Our work revealed two major knowledge gaps. Marine species records come from occasional sampling campaigns, and we suggest that this group calls for a more systematic research. More work has been done on freshwater species, which revealed many taxonomic uncertainties that cannot be resolved at present and call for additional taxonomic research.